2020
DOI: 10.1177/0972558x20913699
|View full text |Cite
|
Sign up to set email alerts
|

Somatotype Characteristics of Sunni Muslim Population: A Cross-sectional Study

Abstract: The aim of this study was to understand the distribution of various somatotype components and determine the age- and sex-related variations of the somatotype among Sunni Muslim population of Uttar Pradesh, India. The study population consisted of 214 individuals (100 males and 114 females), belonging to the age group of 18–73 years. All somatometric measurements were taken according to the protocol of the International Society for the Advancement of Kinanthropometry (ISAK). Anthropometric somatotyping was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The result of this study reveals that generalized and central obesity was prevalent in the studied population. In line with our current study, a previous study on this population reported high adiposity content with predominantly endomorphic components in their body build (Shimrah et al, 2020). The reason for high prevalence of obesity might be due to lack of physical activities, and shifting of low calorie diet into the high-calorie diet in developing countries (Popkin et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study reveals that generalized and central obesity was prevalent in the studied population. In line with our current study, a previous study on this population reported high adiposity content with predominantly endomorphic components in their body build (Shimrah et al, 2020). The reason for high prevalence of obesity might be due to lack of physical activities, and shifting of low calorie diet into the high-calorie diet in developing countries (Popkin et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, studies have also been conducted to find out the association of somatotype with arterial hypertension (Koleva et al 2002), abdominal adiposity (Williams et al 2000;Ramos-Jiménez et al 2019), blood pressure (Kalichman et al 2004), type 2 diabetes (Baltadjiev 2013;Urrutia-García et al 2015) etc. In India, the studies on somatotype are mostly on population variations in terms of age and sex variation -mainly conducted among children, adolescents and women (Gaur and Singh 1997;Gaur et al 1999;Gakhar and Malik 2002;Dkhar 2005;Bhasin and Jain 2007;Singh 2011;Srivastava et al 2012;Chandel and Malik 2012;Roy and Kundu Chowdhury 2013;Longkumer 2014;Kaur and Malik 2016;Kaur et al 2018;Chandel et al 2018;Mallick et al 2018;Shimrah et al 2020). However, such studies especially in adult tribal populations, are very few and far between (Ghosh and Malik 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Email: ardo.oku@fik.unp.ac.id Muslim women and in men the balanced endomorph [38]. Based on research reviews, it can be concluded that the endomorphmesomorph body type is more in sports that require defense.…”
Section: Ardo Okilandamentioning
confidence: 99%